PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PROGRAM PEMBANGUNAN DESA RANAH BARU KECAMATAN KAMPAR KABUPATEN KAMPAR - Sadila Rahayu; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
study the phenomenon is manifested in the lack of enthusiasm in thecommunity development program undertaken, ranging from determination of the development programs to the construction implements selected. This study aims to determine the level of Community Participation in Rural Development Programme Implementation New realm Kampar Kampar district, and to determine the factorsthat influence the level of community participation in the village of New Realm.Concepts used in this study is according to Cohen and Uphof in Dwiningrumwho say that participation can be distinguished as follows: participation in decision making, participation in the implementation, participation in decision-benefits, participation in the evaluation, and in this study the authors wanted to focus onparticipation in the implementation of development. Descriptive qualitative researchmethods. To perform data collection, this study using interviews, observation, anddocumentation.From the results it can be seen that the Community's Participation in Rural Development Programme Implementation New Domains Kampar Kampar district is still in the category of